Modo de vida na várzea: políticas sociais e nova ruralidade: estudo em uma localidade da Reserva de Desenvolvimento Sustentável Mamirauá - CORRÊA, Dávila Suelen Souza (Universidade Federal do Pará, 2014)
This dissertation is a study on the sustainable development measures and policies for small non-agricultural rural populations, from the 80s and 90s. With the policies reaching the countryside, the state is more present in the smaller regions resizing the countryside and its local dynamics. In this sense, emerges a new rural with the policy actions that reach the most distant population exposing their way of life to new situations. This study aimed to analyze changes in social and economic organization of the inhabitants of rural population of Vila Alencar in the Mamirauá Reserve for Sustainable Development (MRDS), Amazonas State, due to the foundation of a Sustainable Development Reserve (SDR) and institutionalized actions by state policies. The theoretical analysis was based on the theories of habitus and socio-environmental field Reserve Mamirauá. There were also analysis among families from the time of marital union, in order to identify the changes between two generations. It was discovered in this study that the family organization in Vila Alencar is developed taking into account local practices and also participate in the interventionist actions through social policies through the Family Grant Program, the rural pension and activities around the sustainable management of resources natural, these are mainly associated with the ecotourism management, such as the provision like tour guide, kitchen helpers, maid and carpentry for the ecotourism lodge of MRDS. The combination of agricultural, nonagricultural and supplementary income from social benefits have an important role in the composition of household income, which brings new perspectives to social reproduction. The study concludes that sustainable development policies and the policies of social benefits become pro-family organization on rural areas modernizing the characteristics of features and attractive urban comfort, particularly the expectation of buying a house in town and better conditions for qualification for the children to thrive in any profession. To young people are delegated other responsibilities that do not go within the productive context of family labor.